Addressing the Saturation Attainment Controversy: Evidence from the Qualitative Research on Assessing the Feasibility of Informal Sector Taxation in Zimbabwe - Mpofu, Favourate Y (Technium Social Sciences Journal, 2021)
Qualitative Research (hereafter QR) frequently stimulates a great deal of questions and queries on sampling guidelines (techniques, sample sizes and adequacy of samples), data collection as well as analysis. Saturation has been considered a fundamental yardstick to help answer the problematic questions on sampling decisions and to boost validity and rigor in QR. Notwithstanding this, contemporary literature exploring the achievement of saturation point has been comparably sketchy. Most qualitative researchers refer to having reached the point of saturation at some instance in their studies, but without adequately expounding on how and when. This paper documents the steps taken towards reaching saturation and adds to the debate on the body of knowledge on practicable guidelines on how QR can communicate and publish details on the point of saturation. The study is part of a bigger study that adopted a sequential exploratory mixed method research design to evaluate the practicability of taxing the informal sector in Zimbabwe. The qualitative component was employed to gather data and analyse qualitative data, of which the outcomes were used to develop and refine quantitative research instruments (questionnaires) to elicit information on a larger sample. Using data from in-depth interviews with various stakeholders, the study explains how saturation point was achieved during thematic analysis of data and demonstrates how saturation was conceptualised. The study gives a contextual background information on the study (in order to sufficiently situate it), data collection methods and sampling decisions. The study was motivated by the fact that taxation is both a numbers and qualitative information game, yet there are few studies in the finance discipline, especially taxation, that focus on the highly contested saturation concept, its attainment and its reporting in the final publications. The study only focuses on the methodology adopted and how it helped achieve saturation and does not delve into the results of the study in detail.